HUMAN RESOURCE STRATEGY IN FACING FREE TRADE ERA - Sojanah, Janah (Program Studi Pendidikan Manajemen Perkantoran, 2010)
Free Trade ASEAN-CINA which1 January 2010 will make many national industries closed down because failing to competes. As a result, unemployment number is estimated to leaps. Company also tends to economized production cost through usage thrift of permanent labour, so that job security labour becomes fragile and unemployment number is estimated to increases. To answer the challenge, hence needing existence of strategy which must be applied especially relates to human resource. This article tries to analyze about idea related to preparation strategy of human resource in facing free trade era. To reach that thing will be studied about how free trade era evaluated from hope and reality, and how Indonesia human resource strategy in global emulation?